Composition of yoga-philosophy based mental traits (Gunas) in major psychiatric disorders: A trans-diagnostic approach - Bhargav, Hemant; Eiman, Najla; Jasti, Nishitha; More, Pooja; Kumar, Vinod; Holla, Bharath; Arasappa, Rashmi; Rao, Naren P.; Varambally, Shivarama; Gangadhar, B.N.; Keshavan, Matcheri S. (Frontiers in Psychology, 2023)
Yoga philosophy includes the theory of Tri-guna (three mental traits): sattva (signifies attachment to ‘goodness’), rajas (tendency towards ‘activity’), and tamas (tendency towards “inertia”). This cross-sectional study aimed to understand the differences in the expression of gunas in patients suffering from major psychiatric disorders (n = 113, 40 females) and age-gender-education-matched healthy controls (HCs; n = 113, 40 females). Patients were diagnosed by a psychiatrist using DSM 5 criteria and suffered from following disorders: depression (n=30), schizophrenia (SCZ; n=28), obsessive-compulsive disorder (OCD; n=23), anxiety (n=16), and bipolar affective disorder (BPAD; n=16). Tri-gunas were assessed using a validated tool (Vedic Personality Inventory), and symptoms were assessed using standard scales as per the diagnosis. Multi-variate analysis of variance (MANOVA) was used to assess the differences in guna scores between HCs and patients and between patients with different diagnoses. A two-tailed Pearson correlation was performed between the gunas and psychometric scales. Results revealed that HCs had significantly higher sattva traits as compared to patients (except those with OCD). Each psychiatric diagnosis also showed a specific guna configuration: 1) Anxiety disorders and OCD: High sattva-rajas, low tamas; 2) Depression: High sattva-tamas, low rajas; 3) Psychotic disorders (SCZ/BPAD): High tamo-rajas, low sattva. Significant positive correlations were observed between rajas traits and anxiety/OC/positive psychotic symptoms, negative psychotic symptoms and tamas traits, and sattva traits and OC symptoms. This finding has clinical implications, both to develop ways of predicting outcomes of psychiatric disorders, as well as to develop psycho-therapeutic and lifestyle interventions targeting the gunas.